2018
DOI: 10.1177/0037768617747505
|View full text |Cite
|
Sign up to set email alerts
|

Fixity and flux: A critique of competing approaches to researching contemporary Jewish identities

Abstract: Jewish identities are becoming increasingly pluralised due to internal dynamics within Judaism and wider social processes such as secularisation, globalisation and individualisation.However, empirical research on contemporary Jewish identities often continues to adopt restrictive methodological and conceptual approaches that reify Jewish identity and portray it as a 'product'for educational providers and others to pass to younger generations. Moreover, these approaches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“… 2005 , Samson et al. 2018 ). The majority of those interviewed indicated that they identified more with secular Judaism and so looked to Temple Beth El as a locus of ethnic and cultural community.…”
Section: Discussionmentioning
confidence: 99%
“… 2005 , Samson et al. 2018 ). The majority of those interviewed indicated that they identified more with secular Judaism and so looked to Temple Beth El as a locus of ethnic and cultural community.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the likelihood that individuals hold widely varying perspectives and experiences of security concerns, rooted in unique places and potentially differentiated by religious identification, as well as the fact that security and securitization are social constructions (Malmvig 2005 ), qualitative methods appear preferable in revealing this subject’s inherent nuances, as Scheitle and Ulmer ( 2018 ) have started to tease out. Qualitative methods are also better suited to exploratory research such as this, as surveys (for instance) risk applying normative categories that reflect the researcher’s assumptions rather than offering the necessary space for individuals to express their own perspectives (Samson et al 2018 ). Accordingly, semi-structured interviews were used in order to allow respondents to express their concerns, explain their strategies and identify issues of personal importance with far greater freedom than methods such as surveys would have permitted.…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary understandings of Jewish identity see Jewishness through a situational, communal and societal lens. Jewish identity is seen as hybrid or multifaceted, made up of a variety of religious, cultural, genealogical and political configurations that are constantly evolving and unfolding throughout an individual's life [4,6]. The lived experience of Jewishness also transforms in response to changing wider societal contexts, concerns and subjectivities in different settings; the way an American Jew conceptualizes their Jewishness is different to the way an Israeli Jew does [48].…”
Section: Contemporary Views On Jewish Identitymentioning
confidence: 99%
“…Unlocking the individual 'complications' of Jewishness became key to understanding what Jewish identity 'meant' in the life of this community and its interactions with the wider world. As Samson et al [6] argue, "greater attention to individual identity is valuable not only as a way of collecting multiple personal accounts but also as a way of developing complex understandings of individuals' attempts at reworking and redefining (rather than simply reproducing) Jewishness". It became evident that undertaking an informed qualitative study of life in this Jewish community required a means of getting to the heart of how community members qualified their own Jewishness in order to 'live' it.…”
Section: Introductionmentioning
confidence: 99%